SemiSPECT: A small-animal single-photon emission computed tomography (SPECT) imager based on eight cadmium zinc telluride (CZT) detector arrays - Kim, Hyunki; Furenlid, Lars R.; Crawford, Michael J.; Wilson, Donald W.; Barber, H. Bradford; Peterson, Todd E.; Hunter, William C. J.; Liu, Zhonglin; Woolfenden, James M.; Barrett, Harrison H. (Medical physics (Lancaster), 2006)
The first full single-photon emission computed tomography (SPECT) imager to exploit eight compact high-intrinsic-resolution cadmium zinc telluride (CZT) detectors, called SemiSPECT, has been completed. Each detector consists of a CZT crystal and a customized application-specific integrated circuit (ASIC). The CZT crystal is a 2.7 cm × 2.7 cm × ∼ 0.2 cm slab with a continuous top electrode and a bottom electrode patterned into a 64 × 64 pixel array by photolithography. The ASIC is attached to the bottom of the CZT crystal by indium-bump bonding. A bias voltage of − 180 V is applied to the continuous electrode. The eight detectors are arranged in an octagonal lead-shielded ring. Each pinhole in the eight-pinhole aperture placed at the center of the ring is matched to each individual detector array. An object is imaged onto each detector through a pinhole, and each detector is operated independently with list-mode acquisition. The imaging subject can be rotated about a vertical axis to obtain additional angular projections. The performance of SemiSPECT was characterized using Tc 99 m . When a 0.5 mm diameter pinhole is used, the spatial resolution on each axis is about 1.4 mm as estimated by the Fourier crosstalk matrix, which provides an algorithm-independent average resolution over the field of view. The energy resolution achieved by summing neighboring pixel signals in a 3 × 3 window is about 10% full-width-at-half-maximum of the photopeak. The overall system sensitivity is about 0.5 × 10 − 4 with the energy window of ± 10 % from the photopeak. Line-phantom images are presented to visualize the spatial resolution provided by SemiSPECT, and images of bone, myocardium, and human tumor xenografts in mice demonstrate the feasibility of preclinical small-animal studies with SemiSPECT.